2012
DOI: 10.1002/jbmr.1680
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fractures and avascular osteonecrosis in type 1 Gaucher disease: A study from the International Collaborative Gaucher Group (ICGG) Gaucher Registry

Abstract: We hypothesized that overall disease activity or the severity of involvement of individual disease compartments, as measured by clinical and surrogate markers, predict the risk of avascular osteonecrosis (AVN) or fractures in type 1 Gaucher disease (GD1). We applied our risk‐set matched case‐control method to identify four patient groups within the International Collaborative Gaucher Group (ICGG) Gaucher Registry based on the presence and absence of AVN and fractures. Characteristics of GD1 were examined by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 47 publications
(65 reference statements)
2
53
0
2
Order By: Relevance
“…Low bone mineral density of the lumbar spine has been shown to be a risk factor for fractures in patients with Gaucher disease (Khan et al 2012). Wenstrup and colleagues showed that treatment with imiglucerase is associated with an increase in BMD T-scores in a dosedependent manner, but the changes could take years to materialize (Wenstrup et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low bone mineral density of the lumbar spine has been shown to be a risk factor for fractures in patients with Gaucher disease (Khan et al 2012). Wenstrup and colleagues showed that treatment with imiglucerase is associated with an increase in BMD T-scores in a dosedependent manner, but the changes could take years to materialize (Wenstrup et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Osteopenia is the most common feature and along with bone pain together is more prevalent in patients that have had a splenectomy (Charrow et al 2000). Osteopenia in patients with a lumbar spine dual X-ray absorptiometry (DXA) z-score less than or equal to -1.0 can increase the risk of fracture at any skeletal site (Khan et al 2012). Infiltrative disease, from Gaucher cells, can damage bone architecture, most commonly affects the spine and one of the reasons why disease control should be achieved as soon as possible (Wenstrup et al 2007;Charrow et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Importantly, a study of a large cohort revealed that anemia was the only risk factor for avascular osteonecrosis, the most debilitating skeletal complication for GD type 1 patients. 12 Anemia affects 36% of GD patients. 13 The underlying mechanism has not been fully described, although it has been generally attributed to hypersplenism and splenic sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…Since its launch in 1991, the registry has collected data from over 6,500 patients in more than 60 countries, resulting in numerous publications and increased knowledge of the natural history of the disease, phenotypic and genotypic variation among patients, diagnosis and treatment patterns, and long-term outcomes. [8][9][10] Multi-national registries can also provide valuable information for more prevalent conditions. Consider GARFIELD-AF (Global Anticoagulant Registry in the FIELD-Atrial Fibrillation), which was designed to evaluate the management and outcomes of patients with newly diagnosed non-valvular atrial fibrillation (AF) and at least one additional risk factor for stroke.…”
mentioning
confidence: 99%